Transformation of Javanese Song Lyrics and Their Representation in Maintaining Local Language in the VUCA Era - Rumtini; Sulistyo, Hary (International Proceedings of Nusantara Raya, 2024)
This paper discusses the transformation trend of Javanese songs that can represent postmodernism following the development of the internet, social media, and other digital technologies. This phenomenon is interesting to study because the Vuca posture (Volatility, Uncertainty, Complexity, and Ambiguity) is characterized by conditions full of uncertainty, chaos, ambiguity, and complexity that touch almost all aspects of life, including the world of music. This paper aims to a. inventory the singers as representatives of Javanese music characterized by dialects; and b. discuss the transformative contextualization of the trend of Javanese songs with Vuca conditions. Through a qualitative descriptive approach, this study produces a. inventory of Javanese singers as a transformative form of postmodernity in Vuca conditions; b. transformative trend of Javanese songs with East Javanese and Yogya-Soloan dialects, which successfully provide options in the context of maintaining culture, especially Javanese, in the Vuca era which is full of uncertainty over the identity and representation of the country's culture due to the unstoppable rise of other popular music, both foreign and local. This transformation can potentially be a model for other regional language music.